ESTIMATION OF ECONOMIC EXPEDIENCY OF «BRIDGE-PRE-BRIDGE TERRITORY» SYSTEM - A. A. Lapko; V. E. Khizhniak; E. S. Agranovich-Ponomaryova (Наука и техника)
The paper considers principles that form «Bridge-Pre-Bridge Territory» system. The method is proposed for calculation of expenses on technical research for development of projects on usage of pre-bridge territories. Usage of site class number for natural conditions makes it possible to estimate investment attractiveness of «Bridge-Pre-Bridge Territory» system.